Tingkat Pengetahuan Petani Tentang Sinar Ultra Violet Terhadap Kesehatan Mata - Jaja Muhammad Jabbar; Silvy Nursafitri (Sehat MasadaJurnal, 2019)
The sunlight is polychromatic, consists of various electromagnetic wave such as UV light. For some people who has outdoor activities in their daily life, like the farmers, they will receive the sunlight emission more than people who has indoor activities. It causes they are be more vulnerable to get UV light effect, such as damage on eyelid, cornea, lens, and retina. The purpose of this research is to know the farmers’ knowledge related to the source and danger of UV light, also eye protector from UV light. This research is done in Subang. The method that used in this research is descriptive quantitative, which the data from research sample is analyzed corresponding to statistic method that being used. The sample of this research is 78 farmers, who were given a questionnaire consists of 15 questions related to UV light. The result of this research is that the level of farmers’ knowledge related to the source of UV light (77,4%), danger of UV light (49,2%), and eye protector from UV light (70,8%). In general, the level of farmers’ knowledge related to the eye health is good enough (65,5%).